Are Current Prudential Frameworks Up to the Challenge of Climate Risks? - Paola D'Orazio (Intereconomics, 2023)
Climate and environmental issues will likely impact the financial system's stability as they become more pervasive and tangible. As a result, the appropriate financial regulatory and supervisory measures must be in place. This article discusses the challenges faced by financial institutions and the financial system due to the materialisation of climate and environmental risks and the shortcomings in current prudential frameworks. The arguments presented suggest that if the fundamental goal of the Paris Agreement-aligned transition is to phase out coal-fired energy, reduce oil and gas use, and transform carbon-intensive businesses, improving bank governance supervision and/or fostering climate-related disclosure requirements may not be enough. A critical role is instead played by capital requirements that adequately consider climate risks. Moreover, since microprudential tools are typically focused on direct exposures, they may not be sufficient to address the systemic dimension of climate risks. Macroprudential measures should therefore not be overlooked.
Keywords: E44; E50; E58; 330; financial system; stability; climate change; international climate policy; Finanzsystem; Stabilität; Klimawandel; Internationale Klimapolitik